2006
DOI: 10.1038/sj.bjc.6602938
|View full text |Cite
|
Sign up to set email alerts
|

Editing of hnRNP K protein mRNA in colorectal adenocarcinoma and surrounding mucosa

Abstract: The heterogeneous nuclear ribonucleoprotein K (hnRNP K) protein is an RNA-binding protein involved in many processes that compose gene expression. K protein is upregulated in the malignant processes and has been shown to modulate the expression of genes involved in mitogenic responses and tumorigenesis. To explore the possibility that there are alternative isoforms of K protein expressed in colon cancer, we amplified and sequenced K protein mRNA that was isolated from colorectal cancers as well as from normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 35 publications
1
36
0
2
Order By: Relevance
“…Among them, C-to-T and G-to-A were the most frequent (25.3% and 22.5%, respectively), followed by T-to-C (11.6%). Individual examples of C-to-T, G-to-A, and T-to-C editing were reported previously (16)(17)(18). The distributions of the non-A-to-G editing types were similar between the nucleus and the cytosol and between Alu and non-Alu sites (Fig.…”
Section: Resultsmentioning
confidence: 59%
“…Among them, C-to-T and G-to-A were the most frequent (25.3% and 22.5%, respectively), followed by T-to-C (11.6%). Individual examples of C-to-T, G-to-A, and T-to-C editing were reported previously (16)(17)(18). The distributions of the non-A-to-G editing types were similar between the nucleus and the cytosol and between Alu and non-Alu sites (Fig.…”
Section: Resultsmentioning
confidence: 59%
“…In addition, A-to-I editing can play important roles in regulating gene expression , such as by altering alternative splicing (Rueter et al 1999;Laurencikiene et al 2006;Schoft et al 2007), miRNA sequences (Kawahara et al 2007(Kawahara et al , 2008Reid et al 2008;Dupuis and Maas 2010), or miRNA target sites in the mRNA (Liang and Landweber 2007;Borchert et al 2009). Other types of putative RNA editing events are also known, for example, C-to-U editing and U-to-C and G-to-A conversions (Nutt et al 1994;Sharma et al 1994;Villegas et al 2002;Klimek-Tomczak et al 2006), but with much less prevalence.…”
mentioning
confidence: 99%
“…Furthermore, we and others have found that there are other types of RNA-DNA sequence differences (RDDs) that are unlikely to be mediated by these deaminases (Li et al 2011;Bahn et al 2012;Bar-Yaacov et al 2013;Rubio et al 2013;Turner et al 2015). These events are found in normal cells, and altered patterns of RDDs were found in neurologic diseases (van Leeuwen et al 1998;Silberberg et al 2012;Krestel et al 2013;Wang et al 2014) and in cancers (Klimek-Tomczak et al 2006;Martinez et al 2008;Lee et al 2013;Avesson and Barry 2014;Han et al 2014;Niavarani et al 2015). Although differences between RNA and their corresponding DNA templates were known for many years, their discoveries in human beyond the editing events mediated by ADAR and APOBEC families of deaminases were debated.…”
mentioning
confidence: 99%